Communication Skills among the Fourth-Year Medical Students - Jarurin Pitanupong; Arnont Wittayanont (Journal of Health Science and Medical Research (JHSMR), 2013)
Objective: To evaluate the communication skills of fourth-year medical students with their patients and to identify the association of sex and rotating groups of students with these skills among the fourth-year medical students. Material and Methods: This was a prospective descriptive study. The students assessed themselves on communication skills using an anonymous and self-administered questionnaire at three points of time during class study periods. Data were analyzed using descriptive and repeated measures ANOVA. Results: We evaluated 127 students with a mean age of 21.6 years and an average grade of 3.3. About 74% of all students reported that they used communication skills to interview patients more than in other situations. The results showed that the communication skills of students categorized into 5 different subtypes were significantly improved over time (p<0.001). In addition, doctor-patient relationships apparently improved by the end of the class. While communication obstacles clearly decreased, sex and rotating groups of students were not associated with communication skills among the fourth-year medical students. Conclusion: The communication skills of students significantly improved over time. Sex and rotating groups of students were not associated with communication skills among the fourth-year medical students.